PENGARUH MANAGEMENT CHANGE, UKURAN PERUSAHAAN, DAN OPINI AUDIT TERHADAP AUDITOR SWITCHING - Rahmadhani Diea Nuraulia; Menik Indrati (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study is to analyze the effect of management change, company size, and audit opinion on auditor switching. The independent variables of management change, audit opinion and the dependent variable of auditor switching are calculated using dummy variable measurements, while the independent variable firm size is measured by measuring the logarithm of total assets. This research was conducted using a purposive sampling technique using a sample of transportation sub-sector companies listed on the IDX from 2018 to 2021 and obtained 15 companies that met the research criteria with a total of 60 annual report data as observation material. The data analysis method that researchers use is logistic regression analysis. The results of this study state that partially management change, company size and audit opinion do not have a significant positive effect on auditor switching. This research can be a consideration for investors and shareholders to pay more attention to their financial reports, especially to the results of audits issued by companies with the aim that new investors or prospective investors are not wrong in choosing investment decisions. For companies to be more thorough in making or selecting decisions in conducting auditor switching. And for auditors with this research it is hoped that they will not establish cooperative relationships that are too long with clients that can interfere with the auditor's independence.